2016
DOI: 10.5812/ijhrba.27831
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Components of Noncommercial Alcohol Beverage Samples: A Study With the Viewpoint of Toxic Components in Mashhad, Iran

Abstract: BackgroundIran has one of the lowest alcoholic beverage use rates in comparison with other countries, because it is legally forbidden and because of religious beliefs. Even so, unrecorded and noncommercial alcohol remains a considerable concern, which needs special attention.ObjectivesIn the current research, we have studied the general composition of noncommercial alcohol samples to identify potentially toxic components in the context of the city of Mashhad in IR Iran.Patients and MethodsUsing a descriptive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…In our study, the organoleptic examination findings highlighted that the pH of the majority of alcoholic beverages was acidic. This data was consistent with that of a previous study [14]. The acidity nature of alcoholic beverages, especially fermented types, is due to the presence of organic acids, such as acetic acid, maleic acid, or tartaric acid [14].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In our study, the organoleptic examination findings highlighted that the pH of the majority of alcoholic beverages was acidic. This data was consistent with that of a previous study [14]. The acidity nature of alcoholic beverages, especially fermented types, is due to the presence of organic acids, such as acetic acid, maleic acid, or tartaric acid [14].…”
Section: Discussionsupporting
confidence: 93%
“…The determination of ethanol concentration in legal alcoholic beverages is a crucial control point from safety and economic concerns [19]. Previous studies have indicated that illegal and unrecorded alcoholic products have higher ethanol levels than those of the legal production [9,14]. These findings are in concordance with our study in which the ethanol mean concentration was detected as 24%v/v.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations